How Does Pricing Affect Customer Attrition? Evidence From Packaged Account Holders. (February 2015) - Bocchialini, Elisa; Ielasi, Federica; Rossolini, Monica
<x xml:space="preserve">Abstract</x> This research analyses the relevance of pricing models for the attrition of retail banking customers. The analysis is based on a dataset of about 24, 000 current account holders at an Italian commercial bank and focuses on their attrition behaviour in the years 2007 and 2008. The aim of the study is to discover the relationship between pricing conditions of packaged current accounts and customer attrition, verifying the differences between the behaviour of younger customers and that of older ones. The findings identify the pricing variables significantly associated with customer loyalty. We discover that customers, and in particular older ones, are less faithful to current accounts characterised by a fixed cost with unlimited free transactions (Disneyworld pricing).